New molecular targets in Hodgkin and Reed-Sternberg cells - Sadaf, Hummaira; Ambroziak, Maciej; Binkowski, Robert; Kluebsoongnoen, Jakkapong; Paszkiewicz-Kozik, Ewa; Steciuk, Jaroslaw; Markowicz, Sergiusz; Walewski, Jan; Sarnowska, Elzbieta; Sarnowski, Tomasz Jacek; Konopinski, Ryszard (Frontiers in Immunology, 2023)
Recent discoveries shed light on molecular mechanisms responsible for classical Hodgkin lymphoma (HL) development and progression, along with features of Hodgkin – Reed and Sternberg cells (HRS). Here, we summarize current knowledge on characteristic molecular alterations in HL, as well as existing targeted therapies and potential novel treatments for this disease. We discuss the importance of cluster of differentiation molecule 30 (CD30) and the programmed cell death-1 protein (PD-1) and ligands (PD-L1/2), and other molecules involved in immune modulation in HL. We highlight emerging evidence indicating that the altered function of SWI/SNF-type chromatin remodeling complexes, PRC2, and other epigenetic modifiers, contribute to variations in chromatin status, which are typical for HL. We postulate that despite of the existence of plentiful molecular data, the understanding of HL development remains incomplete. We therefore propose research directions involving analysis of reverse signaling in the PD-1/PD-L1 mechanism, chromatin remodeling, and epigenetics-related alterations, in order to identify HL features at the molecular level. Such attempts may lead to the identification of new molecular targets, and thus will likely substantially contribute to the future development of more effective targeted therapies.